Trading ahead of treasury auctions - Jean-David Sigaux (European Central Bank (ECB), 2018)
I develop and test a model explaining the gradual price decrease observed in the days leading up to anticipated asset sales such as Treasury auctions. In the model, risk-averse investors expect an uncertain increase in the net supply of a risky asset. They face a trade-off between hedging the supply uncertainty with long positions, and speculating with short positions. As a result of hedging, the equilibrium price is above the expected price. As the supply shock approaches, uncertainty decreases due to the arrival of information, investors hedge less and speculate more, and the price decreases. In line with these predictions, meetings between the Treasury and primary dealers, as well as auction announcements, explain a 2.4 bps yield increase in Italian Treasuries.
Keywords: G11; G12; E43; 330; anticipated supply shocks; supply risk; Treasury auctions; market making